Valorization of Agricultural Waste into Ecological Coal in the Region of Vakinankaratra - Ranaivoson S. L. O.; Rakotomamonjy P.; Razafindramanga A. W; Razafimahefa M.V; Razafindrakoto N.R.F.; Letsara R.; Andriatsilavo M.H.; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina B. (Britain International of Exact Sciences (BIoEx) Journal, 2023)
Ecological charcoal is coal produced from biodegradable residues rich in carbon, mainly from agricultural residues. This charcoal has been obtained with different operations such as carbonization, molding and compacting to obtain briquettes. To ensure the quality of the coal, several analyses were carried out in the laboratories. The physicochemical characteristics such as moisture content, ash content, fixed carbon content; volatile matter index and lower calorific value are analyzed to better exploit their uses. Its exploitation has many advantages especially in the field of health and environment, especially for the reduction of deforestation and air pollution. This research gives 5 varieties of ecological coal obtained by the valorization of agricultural waste in the region of Vakinankaratra, a region located in the highlands of Madagascar and known for its high potentiality in agriculture and livestock. It is about the valorization of rice straw, rice husk, corn straw, banana peelings, and soybean stalks.